Knowledge on Palliative Care of Nurses in Selected Hospitals of Pokhara - Shrestha, Saphalta (NPRC Journal of Multidisciplinary Research, 2025)
Background: Palliative care improves the quality of life of patients and families facing the problem of life. The main objective is to assess the knowledge on palliative care of nurses in selected hospitals of Pokhara. Methods: A descriptive cross-sectional study was conducted in selected hospitals in Pokhara, using a non-probability purposive sampling technique to select the hospitals and wards. The study included a complete enumeration of 175 nurses. A self-administered structured questionnaire was used to gather information on Palliative Care. The data was coded, entered into SPSS version 16, and analyzed using both descriptive and inferential statistics (Chi-square test). Results: The study revealed that 80.6% of nurses were aged between 21 and 30 years, with a mean age of 28.1+6.02 years. More than half (58.9%) had completed PCL nursing. Regarding knowledge of Palliative Care, only 7.4% of respondents had adequate knowledge, and 92.6% had inadequate knowledge. A significant association was found between knowledge levels and age of the respondents. Conclusion: In conclusion, most of the respondents had inadequate knowledge. So, hospitals should implement comprehensive palliative care training to improve nurses' knowledge.